2020
DOI: 10.1093/jxb/eraa020
|View full text |Cite
|
Sign up to set email alerts
|

Three previously characterized resistances to yellow rust are encoded by a single locus Wtk1

Abstract: Temperature of elongation 59°C; Enzyme AciI; Fragment sizes: T. dicoccoides H52 = 266 bp, 148 bp; T. durum cv. Langdon = 414 bp. # Full description of yr15 mutants is provided in Klymiuk et al. (2018). * The first letter indicates the wild-type nucleotide, the number indicates its position relative to the ATG start codon, and the last letter shows the mutant nucleotide. The complete WTK1 coding regions of the above 19 mutants were sequenced; no additional mutations were detected. † The first letter indicates t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…The current histopathology study is part of a long-term project aiming to clone and characterize powdery mildew and stripe rust resistance genes derived from wild emmer wheat by using the map-based cloning approach, as we recently demonstrated for the cloning of Yr15 [14,20]. Previously, we localized PmG3M to chromosome 6B using the G305-3M × LDN mapping population [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current histopathology study is part of a long-term project aiming to clone and characterize powdery mildew and stripe rust resistance genes derived from wild emmer wheat by using the map-based cloning approach, as we recently demonstrated for the cloning of Yr15 [14,20]. Previously, we localized PmG3M to chromosome 6B using the G305-3M × LDN mapping population [12].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence microscopy of Bgt structures was performed using wheat germ agglutinin (WGA; a lectin that binds specifically to β (1→4)-N-acetyl-D-glucosamine, i.e., chitin) conjugated with a fluorescent dye, according to Dawson et al [43] and Klymiuk et al [14,20], with slight modifications. Leaf segments (primary leaf, 5 cm long) were sampled at 4,8,12,18,24,32,48,72,96,120,144,168 and 240 h post inoculation (hpi) with Bgt spores.…”
Section: Microscopic Observations Of Wheat-bgt Interactions Within Inmentioning
confidence: 99%
“…In the present study, we observed a range of resistance responses in wild emmer accessions carrying functional Yr15. Different hypotheses may explain our observation: (1) phenotypic differences in the presence of Yr15 are likely associated to differences in the genetic backgrounds [35];…”
Section: Stripe Rust Resistance Variation In Wild Emmer Accessions Camentioning
confidence: 96%
“…In the present study, we observed a range of resistance responses in wild emmer accessions carrying functional Yr15. Different hypotheses may explain our observation: (1) phenotypic differences in the presence of Yr15 are likely associated to differences in the genetic backgrounds [35]; (2) the presence of suppressors that suppressed Yr15-mediated resistance [36]; (3) absence/mutation of downstream substrates of resistance gene signaling pathway [21,37].…”
Section: Stripe Rust Resistance Variation In Wild Emmer Accessions Camentioning
confidence: 97%
“…So far, Pst resistance genes have been designated [72] and many QTLs identified in wheat have been reported on chromosome 1B [73]. Yr10 [74], Yr9 [75], YrAlp [72], Yr15 [76] , YrH52 [77],…”
Section: Analysis Of the Major Resistance Locus Identified On Chromosmentioning
confidence: 99%